algebraic expression using a2-b2=(a+b)(a-b)
Answers
Answered by
1
(a+b)(a-b)
=> a(a-b) + b(a-b)
=> a^2 - ab + ab - b^2
=>a^2 - b^2
HOPE IT HELPS YOU...
=> a(a-b) + b(a-b)
=> a^2 - ab + ab - b^2
=>a^2 - b^2
HOPE IT HELPS YOU...
Answered by
0
bdbbdbdbdndnjdndndnnd djs shje djnd Jens skin skins innu band dbdbdb you hubby a s shehhehehejejbb @ b jjjjnxbd Hobbs bdjjzjzjnx nhsn Bonn nd g nhan alpam tension but try to complete bbcjjfnjfu nction k bnjfnnfnfnnd blends nhan k g enda paripadi B.C. nhan nale dBm nhan nd u can m c nd cgapter bi
Similar questions